2017
DOI: 10.1111/ffe.12695
|View full text |Cite
|
Sign up to set email alerts
|

Designing pro‐composite truss layout for load‐bearing aircraft structures

Abstract: The frame (truss) layout based on the hybrid metal‐composite rod elements is proposed for weight saving of the primary aircraft structures. It is proposed to provide the durability of rod elements by protection system against impacts and environment. The algorithm of designing the structure with frame layout has been developed on the basis of 2‐level approach. Fast strength analysis methods based on automated numerical models have been developed. The results of comparative weight estimations of frame and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…With respect to the third variant, the weight estimation was performed in parallel with the development of a manufacturing model of the double-lattice panel. In [6,7], it was shown that double-lattice pressurized panels, as described above, could create a low-weight airframe for the BWB with a high operational reliability. The application of such panels can therefore become the solid foundation for significant improvement in the transport efficiency of future aircraft by using the BWB concept.…”
Section: Critical Strength Tasks Of Bwb Airframesmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the third variant, the weight estimation was performed in parallel with the development of a manufacturing model of the double-lattice panel. In [6,7], it was shown that double-lattice pressurized panels, as described above, could create a low-weight airframe for the BWB with a high operational reliability. The application of such panels can therefore become the solid foundation for significant improvement in the transport efficiency of future aircraft by using the BWB concept.…”
Section: Critical Strength Tasks Of Bwb Airframesmentioning
confidence: 99%
“…The root of the problem of the BWB concept's low weight efficiency are the expenses related to high weight efficiency, namely, the costs needed to ensure the proper strength characteristics of high-loaded pressurized low-curvature (flat) panels. One solution to this problem was proposed in [6][7][8] based on double-lattice composite panels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional metal materials, carbon fiberreinforced composites have such advantages as large specific strength, high specific modulus, high damping, and strong designability [13,[16][17][18]. Currently, the structure forms of CFRP applied to vibration isolation are mostly of the trusstype structure, including satellite, spaceship, and other aerospace structures [9,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Implant structure made of titanium alloy, proposed by D. Pasini, McGill University, 9 provides allowable level of contact loads between the implant and the bone tissue, that minimizes the stress concentrations and by that prevent failure of the bone tissue during exploitation of the implant. One of feasible applications of the proposed ''soft'' joint in aircraft structures is the structure of metalcomposite joint of ''clamp'' type 10 (Figure 12). Metallic part of the joint is placed (like a clamp) on the rod composite element and allows to transfer loads, perpendicular to the main axis of the composite element.…”
Section: Introductionmentioning
confidence: 99%